CEO birth order and corporate social responsibility behaviors: The moderating effect of female sibling and age gap - Zheng, Minna; Ren, Guangqian; Wu, Sihong; Jiang, Zezhen (Frontiers in Psychology, 2022)
The outbreak of COVID-19 pandemic has increased the challenges enterprises faced, while enterprises struggle to amid the economic crisis through various activities. Corporate social responsibility is one of the most important business strategies which helps enterprises to obtain competitive advantage and improve performance. Scholars have done many beneficial researches on the driving factors of CSR behaviors from the perspective of CEO traits, but rarely focus on the impact of CEOs’ early family experiences. This study aims to fill this research gap to investigate the influence of CEO birth order on firms’ CSR behaviors, and further explores the possible moderating effect of the presence of a female sibling and the age gap between CEO and the closest sibling. This study takes Chinese non-financial private listed companies from 2010 to 2017 as the research samples, and empirically tests the relationship between CEO birth order and firms’ CSR behaviors. The empirical results show that CEO birth order negatively influences corporate social responsibility behaviors, and this relationship would be weakened when CEO has a female sibling or the age gap between CEO and the closest sibling is larger. This paper extends the research on personal family factors from the field of social psychology to the business field, and finds a new driving factor of corporate social responsibility behavior from the perspective of CEOs’ early family factors.